MARKETING TRANSFORMATION: BRANDING AND DIGITAL MARKETING STRATEGIES FOR MSMES: MARKETING TRANSFORMATION: BRANDING AND DIGITAL MARKETING STRATEGIES FOR MSMES - Adi, Muh. Husriadi (Noble Cendekia Indonesia, 2025)
This study examines the marketing transformation of coffee shop MSMEs through the integration of branding and digital marketing strategies in facing the challenges of the digital era. The objective of the study is to understand how MSMEs adopt and manage these strategies to improve their competitiveness and business sustainability. A qualitative research method with a case study approach was used, involving in-depth interviews, observation, and documentation with coffee shop MSMEs in Korumba District. The results show that consistent visual identity, customer experience that reflects brand character, and effective use of social media such as Instagram and WhatsApp in sharing creative content play a significant role in expanding the market and building personal relationships with customers. However, limited digital capabilities of human resources, the dynamics of social media algorithms, and limited promotional budgets are the main obstacles that affect the effectiveness of digital marketing strategies. The implications of this study emphasize the importance of developing MSMEs' digital capacity, supporting funding policies, and utilizing adaptive technology as solutions to encourage the growth and sustainability of MSMEs in the digital ecosystem. This study provides relevant empirical contributions to MSME digital marketing theory as well as practical recommendations for business actors and policymakers.